Spastic diplegia in preterm-born children: Executive function impairment and neuroanatomical correlates. (February 2017) - Di Lieto, Maria Chiara; Brovedani, Paola; Pecini, Chiara; Chilosi, Anna Maria; Belmonti, Vittorio; Fabbro, Franco; Urgesi, Cosimo; Fiori, Simona; Guzzetta, Andrea; Perazza, Silvia; Sicola, Elisa; Cioni, Giovanni
Abstract: Background: The neuropsychological literature on preterm-born children with spastic diplegia due to periventricular leukomalacia is convergent in reporting deficits in non-verbal intelligence and in visuo-spatial abilities. Nevertheless, other cognitive functions have found to be impaired, but data are scant and not correlated with neuroimaging findings. Aims: This study analyzes the neuropsychological strengths and weaknesses in preterm-born children with spastic diplegia (pSD) and their relationships with neuroanatomical findings, investigated by a novel scale for MRI classification. Methods and procedures: Nineteen children with pSD, mild to moderate upper limb impairment and Verbal IQ > 80, and 38 normal controls were evaluated with a comprehensive neuropsychological battery (NEPSY-II), assessing Attention/Executive Functioning, Language, Memory, Sensorimotor, Social Perception and Visuospatial Processing domains. The MRIs were quantitatively scored for lesion severity. Outcomes and results: The results showed that, beyond core visuo-spatial and sensory-motor deficits, impairments in attention and executive functions were present in more than half of the sample, particularly in children with damage to the anterior corpus callosum. Conclusions and implications: The findings are discussed in terms of clinical and rehabilitative implications tailored for pSD subgroups diversified for neuropsychological and neuroanatomical characteristics.